Variation in seed metabolites between two indica rice accessions differing in seed longevity - Lee, Jae-Sung; Hay, Fiona R. (MDPI, 2020)
For a better understanding of germination after seed storage, metabolite profiling was conducted using hybrid triple quadrupole time-of-flight (QTOF) mass spectrometry. After moisture content (MC) equilibration, seeds of “WAS170” (short-lived) and “IR65483” (long-lived) were stored at 10.9% MC and 45 °C. Samples for metabolite analysis were taken after 0 and 20 days of storage. Among 288 metabolites, two flavonoids (kaempferide and quercetin-3-arabinoside), one amino acid (S-sulfocysteine) and one sugar (D-glucose) increased in “IR65483” seeds after storage but were not detected in “WAS170” seeds. Based on the genome sequence database, we identified clear allelic differences with non-synonymous mutations on the six flavonol synthase genes regulating the accumulation of kaempferol- and quercetin-metabolites. On the other hand, two metabolites (thiamine monophosphate and harmaline) increased in short-lived seeds after storage; these metabolites could be potential biochemical indicators of seed deterioration.